Benzoyl transfer reactivities of racemic 2,4-Di-O-acyl-myo-inosityl 1,3,5-orthoesters in the solid state: molecular packing and intermolecular interactions correlate with the ease of the reaction - Sarmah, M. P.; Gonnade, Rajesh G.; Shashidhar, M. S.; Bhadbhade, Mohan M. (Chemistry-A European Journal, 2005)
Racemic 2,4-di-O-acyl-myoinosityl 1,3,5-orthoesters undergo transesterification catalyzed by sodium carbonate with varying ease of reaction in the solid state; reactions in solution and melt do not show such varied differences. An interesting crystal of a 1:1 molecular complex of highly reactive racemic 2,4-di-O-benzoyl-myo-inosityl 1,3,5-orthoformate and its orthoacetate analogue exhibited better reactivity than the latter component alone. Single-crystal X-ray structures of the reactants have been correlated with the observed differences in the acyl-transfer efficiencies in the solid state. Although each of the derivatives helically self-assembles around the crystallographic 2(1) axis linked through O-(HO)-O-... hydrogen bonding, the pre-organization of the reactive groups (C=O [El] and OH [Nu]), C-(HO)-O-... and the C=H(...)pi interactions are significantly more favourable for the reactive derivatives than the less reactive ones. Bond-length distributions also showed differences; the O-C bond of the axial benzoyl group, which gets cleaved during the reaction, is longer (1.345-1.361 angstrom) relative to the chemically equivalent O-C bond of the equatorial benzoyl group (1.316-1.344 angstrom) in the reactive derivatives. These bond-length differences are not significant in the less reactive derivatives. The overall molecular organization is different too; the strikingly discrete helices, which may be viewed as ``reaction tunnels'' and are held by interhelical interactions, are clearly evident in the reactive derivatives in comparison with the less reactive ones.
Keywords: hydrogen bonds; Inositol; solid-state reactions; structure elucidation; transesterification

Chelation controlled regiospecific O-substitution of myo-inositol orthoesters: convenient access to orthogonally protected myo-inositol derivatives - Devaraj, Subramanian; Shashidhar, M. S.; Dixit, Shailesh S. (Tetrahedron, 2005)
A general method for the completely regioselective protection of the three secondary hydroxyl groups of orthoester derivatives of myo-mositol, utilizing the subtle differences in reactivity exhibited by its alkali metal alkoxides due to differences in their ability to form chelates, is described. This method provides convenient access to orthogonally protected myo-inositol derivatives. A comparison of the methylation of racemic 4-0-trityl-myo-inositol 1,3,5-orthoformate in the presence of sodium or lithium ions showed that stabilization of the C4-alkoxide by chelation with lithium overrides steric hindrance offered by the C6-axial substituent in deciding the regioselectivity during the nucleophilic O-substitution. (C) 2004 Elsevier Ltd. All rights reserved.

Concomitant dimorphs of tri-O-[p-halobenzoyl]-myo-inositol 1,3,5-orthoformates with different halogen bonding contacts: first order crystal-to-crystal thermal phase transition of kinetic form to the thermodynamic form - Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, M. S.; Sanki, A. K. (Chemical Communications, 2005)
Crystallization of tri-O-[p-halobenzoyl]-myo-inositol 1,3,5-orthoformates from ethyl acetate-petroleum ether solution produced concomitant dimorphs that have different halogen bonding contacts; the kinetic form with C-(BrO)-O-...-C contacts upon heating to 185 degrees C, converts completely to the thermodynamic form with C-(BrOLC)-O-... contacts via crystal-to-crystal first order phase transition.

Identical molecular strings woven differently by intermolecular interactions in dimorphs of myo-inositol 1,3,5-orthobenzoate - Bhosekar, Gaurav V.; Murali, Chebrolu; Gonnade, Rajesh G.; Shashidhar, M. S.; Bhadbhade, Mohan M. (Crystal Growth & Design, 2005)
myo-Inositol 1,3,5-orthobenzoate exhibits polymorphic behavior depending upon the solvent and time allowed for crystallization. Long plates (form I, monoclinic P2(1)/n) are produced on crystallization from methanol, while crystallization from ethyl acetate mostly yielded squarish plates (form II, monoclinic P2(1)/c). The latter could also be obtained by achieving rapid nucleation from a supersaturated solution of methanol. Remarkably, the overall conformation of the individual molecules is very similar in both polymorphs, although free rotations were possible for the phenyl ring and for the three O-H groups. O-H center dot center dot center dot O linked one-dimensional isostructural molecular strings in the two forms weave differently by weak intermolecular interactions to produce the dimorphs. Striking difference is seen in the ``zipping'' of molecular layers via phenyl center dot center dot center dot phenyl contacts; thermodynamic crystals of form I utilize a well-recognized ``edge-to-face'' herringbone pattern, making C-H center dot center dot center dot pi interactions, whereas the kinetic crystals of form II show rather uncommon ``edge-to-edge'' organization, which makes short Ph-H center dot center dot center dot H-Ph contacts.

O-H center dot center dot center dot O-bridged dimers linked via C-H center dot center dot center dot O and C-H center dot center dot center dot pi interactions in 4,6-di-O-benzyl-myo-inositol 1,3,5-orthoformate - Manoj, Kochunnoonny; Devaraj, Subramanian; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, M. S. (Acta Crystallographica Section C-Crystal Structure Communications, 2005)

Short S=O center dot center dot center dot C=O contacts associate diastereomers of 2,4(6)-di-O-benzoyl-6(4)-O-[(1S)-10-camphorsulfonyl]-myo-inositol 1,3,5-orthoformate in their inclusion complexes - Manoj, Kochunnoonny; Sureshan, K. M.; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, M. S. (Crystal Growth & Design, 2005)
Diastereomers of 2,4(6)-di-O-benzoyl-6(4)-O-[(1S)-10-camphorsulfonyl]-myo-inositol 1,3,5-orthoformate are linked via short S=O&BULL;&BULL;&BULL; C=O contacts ranging from 2.890 to 3.140 &ANGS; (sum of the van der Waals radii of O and C atoms 3.22 &ANGS;) in all the inclusion complexes formed with organic guest solvents having a C2 symmetry. Although a search for S= O&BULL;&BULL;&BULL; C=O interactions in the CSD showed a sizable number of structures, this communication recognizes its significance for the first time in the formation of molecular assemblies. In all the crystals in the present study except the solvent-free form, the S=O bond points almost perpendicularly to the Csp2 atom of the C=O group. This was also the most frequently observed geometrical approach in CSD analysis. The solvent-free form shows dimer formation via C-H&BULL;&BULL;&BULL; O interaction, which has longer S=O&BULL;&BULL;&BULL; C=O contacts.

Sulfonate protecting groups. synthesis of O- and C-methylated inositols: D- and L-ononitol, D- and L-laminitol, mytilitol and scyllo-inositol methyl ether - Sarmah, M. P.; Shashidhar, M. S.; Sureshan, K. M.; Gonnade, Rajesh G.; Bhadbhade, Mohan M. (Tetrahedron, 2005)
Syntheses of D- and L-ononitol, D- and L-laminitol, mytilitol and scyllo-inositol methyl ether starting from myo-imositol are described. One or two of the inyo-inositol 1,3,5-orthoformate hydroxyl groups were protected as tosylates. These mono or ditosylates served as key intermediates for the preparation of O- and C-methyl inositols. Racemic 2,4-di-O-tosyl-myo-inositol 1,3,5-orthoformate was resolved as its diastereomeric camphanates. Use of sulfonate groups for the protection of inositol hydroxyl groups resulted in substantial improvement in the overall yield of O- and C-methyl inositols. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Cyclitol; Inositol; Orthoester; Protecting group; sulfonate

Cyclitol based metal complexing agents. preference for the extraction of lithium by myo-inositol based crown-4-ethers depends on the relative orientation of crown ether oxygen atoms - Dixit, Shailesh S.; Shashidhar, M. S.; Devaraj, Subramanian (Tetrahedron, 2006)
myo-Inositol derived crown-4-ethers in which two of the oxygen atoms in the crown ether moiety have different relative orientations were prepared. Metal picrate binding studies revealed that the crown ether having 1,3-diaxial orientation shows the highest selectivity for binding to lithium although the crown ether having 1,2-diequatorial orientation exhibited the highest binding constant for lithium picrate. These results suggest that relative binding affinity of metal ions to crown ethers can be tuned by varying the relative orientation of crown ether oxygen atoms. The relevance of these results to the previously observed regioselectivity during the O-substitution of myo-inositol orthoesters is discussed. (c) 2606 Elsevier Ltd. All rights reserved.
Keywords: crown ether; Cyclitol; Inositol; ligand; lithium; metal complex

Different interaction motifs of dipolar S = O center dot center dot center dot C = O contacts that associate diastereomers of 2,4(6)-di-O-benzoyl-6(4)-O-[(1S)-7,7-dimethyl-2-oxo-bicyclo[2.2.1]heptan-1-ylmethyl]-sulfonyl-myo-inositol 1,3,5-ortho-acetate - Manoj, Kochunnoonny; Gonnade, R. G.; Bhadbhade, Mohan M.; Shashidhar, M. S. (Acta Crystallographica Section C‐Structural Chemistry, 2007)
Diastereomeric mixtures of 2,4(6)-di-O-benzoyl-6(4)-O-[(1S)-10-camphorsulfonyl]-myo-inositol 1,3,5-orthoesters associate in their crystal structures via different geometries of S=O...C=O short contacts, depending upon the substitution. A comparison of the dimeric association in the orthoacetate and orthoformate (solvated) derivatives shows a sheared parallel motif of dipolar S=O...C=O contacts bridging the former, whereas perpendicular S=O...C=O contacts occur in the latter. The title compound, C32H34O11S, is chiral, owing to the presence of the camphor moiety.

Dipolar S=O center dot center dot center dot C=O and C-H center dot center dot center dot O interactions in the molecular organization of 4,6-di-O-acetyl-2-O-tosyl-myo-inositol 1,3,5-orthoesters - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, M. S. (Acta Crystallographica Section C-Crystal Structure Communications, 2009)
In the absence of conventional hydrogen bonding, the molecules of 4,6-di-O-acetyl-2-O-tosyl-myo-inositol 1,3,5-orthoformate, C(18)H(20)O(10)S, (I), and 4,6-di-O-acetyl-2-O-tosyl-myo-inositol 1,3,5-orthobenzoate, C(24)H(24)O(10)S, (II), are associated via C-H center dot center dot center dot O interactions. Molecules of (II) are additionally linked via dipolar S=O center dot center dot center dot C=O contacts. It is interesting to note that the sulfonyl O atom involved in the dipolar S=O center dot center dot center dot C=O contacts does not take part in any other interaction, indicating the competitive nature of this contact relative to the weak hydrogen-bonding interactions.

Conformational polymorphism in racemic 2,4-Di-o-Benzoyl-6-o-Tosyl myo-Inositol 1,3,5-Orthoacetate - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, M. S. (Journal of Structural Chemistry, 2010)
The title compound, C(29)H(26)O(10)S, yields two conformational polymorphs concomitantly from dichloromethane-methanol mixture; the major polymorph grows as plates (Form I, monoclinic, P2(1)/n) and the minor polymorph grows as needles (Form II, triclinic, P-1). The two forms differ mainly in orientation of the tosyl group. In Form I, sulfonyl oxygen of the tosyl group makes intermolecular C -HaEuro broken vertical bar O interactions, whereas the same group in Form II is involved in an intramolecular short dipolar S=OaEuro broken vertical bar C=O (sulfonyl-carbonyl) contact. The molecular organization and the influence of various weak non-covalent interactions that stabilize these conformers in the crystal lattices are discussed.
Keywords: Conformation; crystal structure; dipolar interactions; Inositol; non-covalent interactions; polymorphism; sulfonyl-carbonyl contact

M. V. Bhatt (1924-2016) - Shashidhar, M. S.; Periasamy, M. (Current Science, 2016)